A Cross-Cultural Study of Collective Brand Perceptions Within The Brand Equity Framework. Issue 3 (3rd July 2017) - Krautz, Carolin
Abstract : Brand equity frameworks conceptualize consumer metrics as individual brand perceptions that are relevant in individualistic cultures. These frameworks require extension to collectivistic cultures to understand collective brand perceptions. Collective brand perceptions form through brand information to which consumers in collectivistic cultures are more susceptible. Are such perceptions culture-bound? Multilevel analysis links two unique consumer samples to answer the question. One represents individual consumer metrics (N = 4, 593); the other reflects collective brand perceptions (N = 10, 090). Collective brand perceptions affect brand choices in collectivistic societies but not individualistic ones. Managerial implications emerge on adapting branding strategies to collectivistic cultures.